Maternal Sadness in the Context of Developmental Disabilities: A Cross-Sectional Study of Autism, Down Syndrome, and Intellectual Disability - Jiu, Cau Kim; Ariyanti, Sri; Wahyuni, Tri; Usman, Usman; Solikhah, Solikhah (Chakra Brahmanda Lentera Institute, 2026)
Background: Mothers of children with special needs are vulnerable to emotional challenges; however, specific emotional responses such as sadness remain underexplored in the literature. This study aimed to describe the levels of sadness among mothers of children with Autism Spectrum Disorder (ASD), Down syndrome, and intellectual disabilities. Methods: A cross-sectional descriptive study was conducted between July and December 2025 involving 62 mothers recruited through purposive sampling. Data were collected using a self-reported questionnaire consisting of 15 Likert-scale items measuring sadness levels. Scores ranged from 0 to 60 and were categorized into four levels. Data were analyzed using descriptive statistics, ANOVA, and chi-square tests with a significance level of p < 0.05. Results: The majority of respondents reported moderate to high levels of sadness. The highest mean sadness score was observed among mothers of children with ASD (M = 49.30), followed by Down syndrome (M = 48.67), both indicating high levels. In contrast, mothers of children with intellectual disabilities reported moderate levels (M = 44.25). There was a significant difference in sadness levels across disability types (p = 0.001). Bivariate analysis showed that maternal education, occupation, family income, and type of disability were significantly associated with sadness levels (p < 0.05), whereas maternal age, child’s age, and gender were not (p > 0.05). Conclusion: Sadness is a prevalent emotional response among mothers of children with special needs, with variations across disability types and socioeconomic factors. These findings highlight the importance of targeted psychosocial support to improve maternal well-being.